Photoisomerization of dicyanorhodanine-functionalized thiophenes - Kornman, Cory T. (Chem Sci, 2020)
π-Conjugated oligomers functionalized with the popular dicyanorhodanine (RCN) electron acceptor are shown to be susceptible to photo-induced Z/E isomerization. The stereochemistry of two model RCN-functionalized thiophenes is confirmed by single crystal X-ray analysis and 2D NMR, and shown to be the thermodynamically stable Z form. Relative energies, Z/E configurations, and conformational preferences are modelled using density functional theory (DFT). The photophysical properties of the model compounds are explored experimentally and computationally; the Z and E isomers display similar absorption profiles with significant spectral overlap and are inseparable upon irradiation to a photostationary state. The well-behaved photoisomerization process is routinely observable by thin-layer chromatography, UV-vis, and NMR, and the photochemical behavior of the two RCN-functionalized thiophenes is characterized under varying wavelengths of irradiation. Ultraviolet (254 nm) irradiation results in photostationary state compositions of 56/44 and 69/31 Z-isomer/E-isomer for substrates functionalized with one thiophene and two thiophenes, respectively. Ambient laboratory lighting results in excess of 10 percent E-isomer for each species in solution, an important consideration for processing such materials, particularly for organic photovoltaic applications. In addition, a photoswitching experiment is conducted to demonstrate the reversible nature of the photoreaction, where little evidence of fatigue is observed over numerous switching cycles. Overall, this work showcases an approach to characterize the stereochemistry and photochemical behavior of dicyanorhodanine-functionalized thiophenes, widely used components of functional molecules and materials.